. - K, KRISHNAVENI; JOHNEY JOHNSON (Turizam, 2026)
Providing exceptional experiences to customers has become a paramount goal of the emerging Hospitality and Tourism industry (H&T) due to its experiential nature. Transcendent customer experience is a dimension of customer experience that refers to exceptional or deeply meaningful interactions that go beyond mere satisfaction to create a lasting emotional connection with a brand or product. This study empirically evaluates the influence of transcendent tourist experience (TTE) on eWOM intention through the mediating role of destination brand love (DBL) within the framework of Stimulus-Organism-Response theory. Using path analysis, this study examined data from 404 tourists who visited Wellness tourism destinations in Kerala. The findings of the study reveal that TTE significantly influence eWOM through the mediation of DBL. It also provides valuable insights for tourism marketers who aim to leverage consumer sentiments to promote destinations online and to focus on improving customer engagement and advocacy through experiential marketing.